Developing an Interpreter for the Implementing STEP-XML Enable Seamless Integration of Design and Additive Manufacturing - M. Lakshmi Sramika (International Journal of Intelligent Systems and Applications in Engineering, 2024)
Additive manufacturing (AM) presents significant advantages for industrial production, particularly in scenarios demanding intricate designs at small scales. Multiple research initiatives are currently advancing to enhance universal data formats. These efforts aim to enable developers and users alike to seamlessly organize, validate, and experiment with complete digital workflows, leveraging AM technologies’ standardized interfaces and data frameworks. A key research focus involves developing an interpreter to convert STEP geometry files into XML format, optimized for compatibility with AM processes. This methodology is validated through practical experimentation using a 3D printer, which tests the interpreter across two distinct case studies. Modern manufacturing systems necessitate strategic methodologies and tools for product design and development. Efficient utilization of equipment and resources requires computational intelligence-based modeling, analysis, and optimization across industrial operations such as planning, design, operation, and control. The future expectations of the industry highlight a seamless process where a customer’s natural language input is directly integrated into CAD/CAM software to generate the final product. This underscores the need for CAD/CAM engineers to incorporate artificial intelligence (AI), digital twin (DT), and allied technologies into the product development cycle. Achieving this integration enhances productivity and enables the production of high-quality, cost-effective products, thereby enhancing competitiveness and sustainability in the global market. This unified approach hinges on the tight integration of AI and digital twin technologies with all systems utilized in design and manufacturing. An interpreter is developed in the present work to integrate design geometry and additive manufacturing.